Role of socio- psychological factors in perceived quality of care rendered by traditional medical practitioners in Ibadan, Nigeria (2013)
Background: It was the aim of the current research to investigate perceived service quality rendered by traditional medical practitioners and the role of socio-psychological factors in the perception. Methods: The first part, a quantitative cross-sectional survey utilized a 93-item questionnaire to examine the influence of quality of life, general health perception, socio-economic status and personality factors on perceived service quality. The second part, a qualitative study utilized 5 FGDs and 2 KIIs to explore consumers’ evaluation of perceived service quality. Five research questions were raised. The 336 purposively-selected participants were attendees of traditional-health clinics/centers in Ibadan with a mean age of Ẋ=30.60± 9.97. Findings: The FGD respondents opined that the scope of orthodox-medicine does not cover certain illnesses. 77.8% of the participants attested to the affordability and promptness of services in traditional hospitals; acknowledging that its perceived efficacy (i.e. 56.8%) motivate patronage of traditional-health service. The 2x2x3 ANOVA revealed significant main effect of quality of life (F[1,270]=41.05, p<.001) and socio-economic status (F[2,270]=36.34; p<.001); as well as interaction effect of quality of life, general health and socio-economic status (F[1,270]=9.624, p<.002); while the regression analysis showed independent influence of extraversion (β=0.31; p<.001), agreeableness (β=0.303; p<.001) and openness to experience (β=0.166; p<.01). Conclusion: This sample acknowledged that traditional health care met quality standards. The role of socio-psychological factors in the quality appraisal was established. The need for better regulation and validation of traditional health care in assuring evidence based care was suggested.